Righting the Resource Curse: Institutional Politics and State Capabilities in Edo State, Nigeria. Issue 2 (1st February 2017) - Porter, Doug; Watts, Michael
Abstract: The poor record of liberal reforms sponsored by the international community in postcolonial settings underscores the real politik of institutional change. What we call a 'new normal' in development policy and practice foregrounds the role of agency – leadership, networks of connectors and convenors, entrepreneurs and activists – but it has less to say about the political and economic conditions of possibility in which agents operate. The putative powers of agency seem most challenged in contexts of extreme resource dependency and the resource curse. The particular case of Edo, a state in the oil rich Niger delta region of Nigeria, illustrates the intersection of agency and structural conditions to show how 'asymmetric capabilities' can emerge to create, constrain and make possible particular reform options.